Discussing implications of fast depleting rural ponds on the globally threatened wetland winter migratory bird in Haryana: a Case Study of Nigdu village pond in Karnal District - Rohtash Chand Gupta; Tirshem Kumar Kaushik (Journal of Tropical Life Science, 2013)
The Nigdu-Sarovar is located in Nilokheri block in Karnal district in Haryana (29°50°N, 76°55°E). The duration of observations span over seven years (September, 2005 to March, 2012). The recording of wetland winter visitor birds during 2005-08 in winter season included atleast 58 species of birds belonging to 10 orders and 18 families. It is important to mention that 29 species of wetland birds were winter migratory, 17 residents, 9 local migratory and three species of wetland birds like Lesser-whistling Duck Dendrocygna javanica, Pheasant-tailed Jacana Hydrophasianus chirurgus and Blue-cheeked Bee-eater Merops persicus were summer migratory. The special features of 2005-06 winter was the huge populations of birds like Northern Shoveller Anas clypeata, Northern Pintail Anas acuta, Common Teal Anas crecca, Spot-billed Duck Anas poecilorhynchus, Common Pochard Aythya ferina, Bar-headed Goose Anser indicus, Greylag Goose Anser anser, Gadwall Anas strepera, Great Cormorant Phalacrocorax carbo, Mallard Anas platyrhynchos and Common Redshank Tringa totanus etc.In successive years, the scenario was more or less a substantial one depicting stability with respect to diversity of birds, number of birds upto the year of 2008. The popular birds included Painted Stork Mycteria leucocephala, Openbill Stork Anastomus oscitans, White-necked Stork Ciconia episcopus, Black-necked Stork Ephippiorhynchus asiaticus, Eurasian Spoonbill Platalea leucorodia, Spotted Greenshank Tringa guttifer and Kentish Plover Charadrius alexandrines. The sharp decline in winter migratory birds at Nigdu-Sarovar started in the year of 2008 when the pond was leased out for FISH-FARMING as per the policies of Govt. of Haryana. Fish Farming based deepening of the pond by excavation of bottom resulting in total decimation of rooted, floating, submerged and ejecting plants along with its subsidiary fauna, Zooplanktons, phytoplankton etc. The age old structural regime of the pond was obliterated to turn it in a scientifically managed fish pond. The year of 2009-10, 2010-11 and 2011-12 (March, 2012) showed the total absence of migratory birds like Mallards, several Geese, Dabbling Ducks, Pochards and Teals etc. As of today (2012), the sarovar is a clean sheet of water with bird repelling devices installed in places.